Biodistribution of Sodium Pertechnetate and Light Microscopy of Organs Isolated from the Rats: Study of the Effects of a Ginkgo biloba Extract - Moreno, S.R.F.; Carvalho, J.J.; Nascimento, A.L.R.; Freitas, R.S.; Dire, G.F.; Lima, E.A.; Lima-Filho, G.L.; Rocha, E.K.; Bernardo-Filho, M. (Pakistan Journal of Nutrition, 2003)
Ginkgo biloba extract (EGb) is a phytoterapic used in the treatment of hypoxic conditions. This medicinal plant has several effects, specially, vasodilator, anti-inflammatory and anti-coagulant properties. It has antioxidant characteristics. Many substances have been reported to affect the biodistribution of different radiopharmaceuticals. We evaluated the influence of an EGb on: (i) the biodistribution of the technetium-99m (Tc-99m) and (ii) on the morphology of the organs from WISTAR rats. The animals were treated (6 days, intra gastric via) with EGb (40 and 400 mg/ml). After that, Tc-99m was injected and the animals were sacrificed. The organs were isolated and counted in a well counter. The percentages of radioactivity per organ (%ATI/organ) and radioactivity per gram (%ATI/gram) of each organ were calculated. Histological preparations were carried out with the pieces of organs (kidney, liver, duodena) withdrawn from the treated animals (400mg/ml EGb). The results showed that EGb altered (not significant, p>0.05) the biodistribution of the Tc-99m in the kidneys and liver. A significant (P<0.05) decrease in the uptake of this radiopharmaceutical in the duodena after the treatment with EGb 40 mg/ml and with EGb 400 mg/ml was observed (%ATI/organ and %ATI/gram). However, this decrease was not capable to alter the optical microscopy of the duodena. Morphological alterations on kidney and liver due to treatment (in vivo) were found. We suggest that the action of EGb could generate metabolites capable to promote modifications in the organs, such as, kidney and liver and to alter the biodistribution of the Tc-99m in the treated animals.